Penentuan Kesesuaian Lahan Tanaman Leci Di Desa Naku Kota Ambon - Charles Silahooy (Faculty of Agriculture, Pattimura University, 2013)
The experiment was conducted to determine and map the land suitability of lychee plant in Naku village. The results showed land units that belong to the class of land suitability (S1) were GD1 and GD2 covering 4.6 ha (2.42%). Land units that included the class of marginally suitable land (S3) was GD4 covering 1.9 ha (1.0%). The limiting factor was the slope of 15-30% and depth of solum 50-75 cm. Not suitable land (N) were the land units GD3, GD5, GD6, GK1, GK2, GK3, GK4 and A1 covering 184.1 ha (96.58%) Limiting factor on the land unit GD3 was depth of solum <50 cm, on GD5 was 30-45% slope, and solum depth of 50 cm, on GD6 was a slope > 45%, on GK1 - GK4 was coarse/very coarse texture, on GK5 was the slope of 30-45 % as well as coarse texture, on GK6 was slope > 45% and very coarse texture, and the limiting factor for the A1 unit was a very coarse texture. The potential land capacity for Lychee plants in Naku Village was area of 6.5 ha or 3.41% of the land area in the Naku village.